Food-borne microbes : shaping the host ecosystem - Jaykus, Lee-Ann; Wang, Hua H. 1965-; Schlesinger, Larry S. (Emerging issues in food safety., 2009)
With contributions from experts in environmental, food, oral, medical, and veterinary microbiology, this book takes an interdisciplinary approach that sheds new light on microbial communities and their interactions within and between different environments, with an emphasis on food systems. The book underscores the role played by food and food-borne microbes in host ecosystem development by connecting complex ecosystems from the environment to the host and linking them to the food carrier.